Review of the Phytochemical and Pharmacological Studies of the Genus Ormocarpum - Nyamboki, Divinah Kwamboka; Wanga, Lucy Aketch (Pharmacognosy Reviews)
Secondary metabolites from medicinal plants play an integral role in the modern drug discovery. Ormocarpum species have been used to effectively manage various disease conditions in both human and animal traditional medicines. This review identifies five species in Ormocarpum namely; Ormocarpum kirkii S. Moore, Ormocarpum sennoides (Willd.) DC., Ormocarpum trichocarpum (Taub.) Engl, Ormocarpum cochinchinense (Lour.)Merr) and Ormorcarpum keninse Gillet. Secondary metabolites in different classes of compounds have been isolated in various studies and are herein reported. This review analyses previously reported data from the ethnomedicinal and pharmacological studies of plants in the genus Ormocarpum.
Keywords: Ormocarpum; Pharmacology; Phytochemistry; Secondary metabolites; Ethnomedicine; Compounds